RISK MANAGEMENT COMMITTEE ATTRIBUTES AND PROFITABILITY OF LISTED DEPOSIT MONEY BANKS IN NIGERIA MODERATED BY OPERATIONAL RISK - Ibrahim Aminu; Professor Samuel Eniola Agbi; Dr. Adzor Ibiamke (Gusau Journal of Accounting and Finance, 2025)
This study investigates the effect of risk management committee (RMC) attributes on the profitability of listed deposit money banks in Nigeria, with a specific focus on the moderating role of operational risk. The aim is to explore how the size and independence of RMCs influence banks' financial performance, and whether operational risk alters this relationship. The analysis draws on data from a sample of thirteen listed banks over a fifteen-year period (2009–2023), using firm-level financial indicators. The findings reveal that the size of the risk committee does not significantly influence profitability, indicating that simply increasing the number of committee members may not enhance financial outcomes. Conversely, risk committee independence, when moderated by operational risk, shows a significant negative effect on profitability, suggesting that excessive independence without sufficient industry expertise may hinder effective decision-making. Operational risk itself exerts a substantial negative impact on profitability, reinforcing the importance of robust internal control systems and proactive risk governance. Interestingly, while the interaction between committee size and operational risk negatively affects profitability, the interaction between committee independence and operational risk shows a positive influence, highlighting the value of balanced and expert oversight. These findings underscore the need for Nigerian banks to strengthen their risk governance structures and for regulators to implement policies that promote a combination of independence and financial expertise in risk committees. The study recommends that banks prioritize effective operational risk management frameworks to safeguard profitability in the face of growing financial and regulatory challenges.